57‐4: Solid State Reflective Display (SRD®) with LTPS Diode Backplane. Issue 1 (29th May 2019) - Castillo, Sergio Garcia; Feng, Lu; Bachmann, Tobias; Bandhu, Lokeshwar; Talagrand, Clement; Triggs, Graham; Didewar, Katrina; Broughton, Ben; QiJun, Yao; Bhaskaran, Harish; Hosseini, Peiman
Abstract : A highly reflective, vividly colored, bistable, two‐state display utilizing ultrathin films of chalcogenide‐based phase‐change materials has been demonstrated. The display exhibits a unique fast thermal switching mechanism activated by electrical pulses delivered by a LTPS diode array fabricated on a commercial TFT‐LCD line with standard process steps. The display has the potential to provide a new class of colorful, low‐power, indoor and outdoor readable displays.